Gene Expression Analysis of miRNA-21 and miRNA-98 in Hepatic Fibrosis: Molecular Mechanisms and Clinical Relevance - Mubark, Nawras Najah (Academia Open, 2025)
General Background: Liver fibrosis, a precursor to cirrhosis, arises from chronic liver injury due to factors such as hepatitis infection, alcohol intake, obesity, and smoking. Specific Background: MicroRNAs (miRNAs), especially miR-21 and miR-98, are increasingly recognized for their regulatory roles in hepatic fibrogenesis. Knowledge Gap: Despite evidence of miRNA involvement in liver fibrosis, data on their gene expression patterns in specific populations, such as Iraqi patients, remain limited. Aims: This study aimed to evaluate the differential expression of miRNA-21 and miRNA-98 in liver fibrosis patients compared to healthy controls, and their correlation with clinical variables, particularly hepatitis B and C infections. Results: In a case-control design with 88 patients and 88 controls, RT-PCR analysis showed upregulation of miRNA-21 (1.15 vs. 0.32) and downregulation of miRNA-98 (1.67 vs. 6.33) in patients (P < 0.05). miRNA expression was higher in HBV patients and in females. Novelty: This is the first study in Iraq to reveal the opposing expression profiles of miRNA-21 and miRNA-98 in liver fibrosis, suggesting sex-specific and viral infection-related modulation. Implications: These findings highlight the potential of miRNA-21 and miRNA-98 as biomarkers for fibrosis severity and targets for therapeutic intervention, particularly in HBV-associated liver disease. Highlight : miRNA-21 is upregulated in liver fibrosis patients, especially with HBV, suggesting a potential role in fibrogenesis. miRNA-98 is downregulated in liver fibrosis, indicating a protective or regulatory function in fibrosis progression. Gender and virus type influence miRNA expression—females and HBV patients show higher gene expression levels. Keywords: miRNA 21, miRNA 98, RT- PCR, Gene expression, Liver fibrosis